PET PACKAGING CHARACTERIZATION BY MEANS OF DIELECTRIC THERMAL ANALYSIS AND IMPEDANCE SPECTROSCOPY - Chamovska, D.; Lazova, D.; Grchev, T.; Cvetkovska, M. (Journal of Engineering & Processing Management, 2011)
Chemical inertness and physical properties like adequate gas barrier, transparency, light weight and good recyclability, have made poly(ethylene therephtalate) (PET) particularly suitable in food packaging applications, especially in beverages and drinking water. However, several studies have shown the presence of compounds not expected a priori in packed food or bottled water and other beverages. One of the possible sources of these substances is a migration of constituents like monomers, catalysts, additives, degradation products, impurities in starting substances etc, from PET packaging. Therefore, migration of possible contaminants from PET, in normal and extreme conditions, is extensively studied and huge amount of data are reported elsewhere. As the migration process from plastics is closely related to the structure and physical properties of the packaging material, the aim of this work was to study structural changes of PET packaging in different media and under different conditions, and to correlate the data with the possibilities for migration of possible contaminants into the food in contact. It was shown that both techniques, especially DETA, could indicate structural changes into the polymer material, under certain conditions related with packaging applications, which could promote migration process.